Analysis of possible improvement of the plasma performance in JET due to the inward spatial channelling of fast-ion energy. (15th May 2018) - Kolesnichenko, Ya.I.; Lutsenko, V.V.; Tyshchenko, M.H.; Weisen, H.; Yakovenko, Yu.V.
Abstract: Effects of the spatial chanelling (SC) of the energy of fusion-produced alpha particles—the spatial transfer of the energy of fast ions by destabilized eigenmodes and delivering this energy to bulk plasma particles (Kolesnichenko et al 2010 Phys. Rev. Lett .104 075001)—on the plasma performance is studied. Analysis is carried out in the assumption that alpha particles located in the peripheral region of the plasma destabilize multiple fast magnetoacoustic modes (FMM) having global radial structure. The FMM with the frequencies close to cyclotron harmonics of alpha particles are considered. It is found that these FMM can be in resonance with the bulk plasma ions and electrons located in the central region of the plasma, delivering the alpha energy to this region. This improves the overall plasma confinement. In addition, it leads to anomalous ion heating when the ion damping of FMM exceeds the electron one. The damping rates of the considered waves are calculated. It is shown that reasonably small amplitude waves can receive and transfer across the flux surfaces as large power density as that required for spatial channelling of a considerable part of fusion energy. The developed theory of the inward spatial channelling is applied to JET experiments carried out during the deuterium–tritium-experiment campaign (DTE1), where presumably anomalous ion heating and improvement of the plasma confinement took place.